2021
DOI: 10.3899/jrheum.211043
|View full text |Cite
|
Sign up to set email alerts
|

How Should We Measure Peripheral Spondyloarthritis?

Abstract: Spondyloarthritis (SpA) is recognized as an overarching spectrum of disease characterized by axial SpA (axSpA), peripheral arthritis, enthesitis, and dactylitis. Despite significant overlap, patients are often characterized as having predominantly peripheral or axial involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…On the other hand, while a recent meta-analysis showed that the diagnostic delay in axSpA is longer for females compared with males (8.8 vs 6.5 years),23–25 our analysis only observed a short difference (6.2 vs 5.6 years), which was not statistically significant. Relating to pSpA and gender differences, previous data were very scarce, and limited to non-adjusted comparisons 4 26. The evaluation of gender differences in PsA is more difficult than in axSpA due to the heterogeneity of the disease, with different articular patterns 27.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, while a recent meta-analysis showed that the diagnostic delay in axSpA is longer for females compared with males (8.8 vs 6.5 years),23–25 our analysis only observed a short difference (6.2 vs 5.6 years), which was not statistically significant. Relating to pSpA and gender differences, previous data were very scarce, and limited to non-adjusted comparisons 4 26. The evaluation of gender differences in PsA is more difficult than in axSpA due to the heterogeneity of the disease, with different articular patterns 27.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed diagnosis can be a critical issue in primary care. The possibility of undifferentiated peripheral SpA should always be considered in patients presenting with acute-onset joint symptoms of unknown origin [ 3 ]. Patients should be referred to a rheumatologist to ensure an effective early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…should always be considered in patients presenting with acute-onset joint symptoms of unknown origin [3]. Patients should be referred to a rheumatologist to ensure an effective early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations